Assessment of a quantitative 5′ nuclease real-time polymerase chain reaction using groEL gene for Ehrlichia and Anaplasma species in rodents in Brazil - Benevenute, Jyan Lucas [UNESP]; Dumler, John Stephen; Ogrzewalska, Maria; Roque, André Luiz Rodrigues; Mello, Victoria Valente Califre [UNESP]; de Sousa, Keyla Carstens Marques [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; D'Andrea, Paulo Sérgio; de Sampaio Lemos, Elba Regina; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2017)
New genotypes of Anaplasmataceae agents have been detected in wild carnivores, birds and deer in Brazil. The present work aimed to investigate the presence of Ehrlichia and Anaplasma species in rodents sampled in Brazil. Additionally, a newly designed quantitative 5′ nuclease real-time multiplex PCR for Ehrlichia and Anaplasma spp. detection based on groEL gene amplification was designed, showing high specificity and sensitivity (10 groEL fragment copy/μL). Between 2000 and 2011, different rodent species [n = 60] were trapped in 5 Brazilian biomes. Among 458 rodent spleen samples, 0.4% (2/458) and 2.4% (11/458) were positive for Ehrlichia and Anaplasma spp., respectively. Of 458 samples, 2.0% (9/458) and 1.1% (5/458) were positive for Anaplasma sp. and Ehrlichia sp., respectively, using conventional 16S rRNA PCR assays. Maximum Likelihood phylogenetic analyse based on a small region of 16S rRNA genes positioned the Anaplasma genotypes in rodents near Anaplasma phagocytophilum or Anaplasma marginale and Anaplasma odocoilei isolates. Ehrlichia genotypes were closely related to E. canis. There was a low occurrence of Anaplasma and Ehrlichia in wild and synanthropic rodents in Brazil, suggesting the circulation of new genotypes of these agents in rodents in the studied areas.